ABO: AS A PREVENTIVE AND INNOVATIVE STRATEGY FOR THE RECONSTRUCTION OF NEW NORMAL IMPLEMENTATION IN THE IMPLEMENTATION OF THE IMMIGRATION SERVICE FUNCTION - Ferdyan Samuel Karunia; Muhammad Rezki Hilmy (Polteknik Imigrasi, 2022)
The increase in the intensity of the occurrence of disasters coupled with the presence of the Covid-19 pandemic caused problems in the process of Examination Reports (BAP) at the Immigration Office Class I Non TPI Bekasi. The problem is in the form of a ban on queues at BAP services due to the increased intensity of passport BAP applicants. This study aims to provide ideas in solving problems including BAP queues. The data collection technique used is pursosive sampling (destination sample). The primary data and secondary data that have been collected are then examined qualitatively to then draw conclusions. The results of this study are that it is necessary to use the Immigration Management Information System (SIMKIM) in creating an online queuing system for the BAP process at the Immigration office, namely through ABO (Online BAP Queue Application).